Advances in polymer electrolyte design strategies for highly efficient supercapacitors and Zn-based batteries - Puthiyaveetil, Priyanka Pandinhare; Babu, Athira; Kurian, Maria; Kurungot, Sreekumar (Chemical Communications, 2025)
Electrolytes play a crucial role in the performance of electrochemical energy storage systems, such as batteries and supercapacitors. Their main function is to act as a medium for ion transport between the electrodes, which is essential for the charge and discharge processes. Beyond this, the electrochemical performance of the device is strongly affected by the various properties of the electrolytes such as their ionic conductivity, chemical, thermal and electrochemical stability, chemical compatibility, etc. The intrinsic limitations of the aqueous electrolytes such as their decomposition during high voltage operations has led to the development of better electrolytes for batteries and supercapacitors. These included non-aqueous electrolytes, inorganic solid-state electrolytes, and gel polymer electrolytes. This feature article reviews the various approaches to designing a highly efficient polymer electrolyte for the targeted application along with the suitable device fabrication strategy adopted in the current literature to achieve a balanced electrochemical performance compared with a liquid electrolyte-based device.